El cuerpo y sus espacios - Salvador, Vicent (Dialogoi. Rivista di studi comparatistici, 2020)
Within the epistemological framework of studies on spatiality, this article examines some aspects related to the human body and the spaces it occupies in the cultural sphere: the symbolisms it creates, its ability to generate metaphors, the inseparable relationship it maintains with the emotional component, the functions that it performs as a mannequin to be dressed or a canvas on which different signs can be inscribed, and finally the human experience of pain and death.